Postencephalitic Parkinsonism: Unique Pathological and Clinical Features—Preliminary Data - Strobel, Sabrina; Sian-Hulsmann, Jeswinder; Tappe, Dennis; Jellinger, Kurt; Riederer, Peter; Monoranu, Camelia-Maria (Cells (Basel, Switzerland), 2024)
Postencephalitic parkinsonism (PEP) is suggested to show a virus-induced pathology, which is different from classical idiopathic Parkinson’s disease (PD) as there is no α-synuclein/Lewy body pathology. However, PEP shows a typical clinical representation of motor disturbances. In addition, compared to PD, there is no iron-induced pathology. The aim of this preliminary study was to compare PEP with PD regarding iron-induced pathology, using histochemistry methods on paraffin-embedded post-mortem brain tissue. In the PEP group, iron was not seen, except for one case with sparse perivascular depositions. Rather, PEP offers a pathology related to tau-protein/neurofibrillary tangles, with mild to moderate memory deficits only. It is assumed that this virus-induced pathology is due to immunological dysfunctions causing (neuro)inflammation-induced neuronal network disturbances as events that trigger clinical parkinsonism. The absence of iron deposits implies that PEP cannot be treated with iron chelators. The therapy with L-Dopa is also not an option, as L-Dopa only leads to an initial slight improvement in symptoms in isolated cases.